Kajian Pemikiran Cendikiawan Muslim dari Al-Kindi Hingga Abduh (Review Buku Khazanah Intelektual Islam Karya Nurcholish Madjid) - Wiji Nurasih; Doli Witro (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padngsidimpuan, 2022)
Throughout the course of Islamic civilization, Muslims have experienced various kinds of dynamics of life. Islam once stood at the pinnacle of civilization before the Islamic world finally realized its backwardness from the Western world. In the golden age of Islam, the progress of Islamic scholarship was much enlivened by the thoughts of Muslim scholars. Likewise, when the Islamic world began to recede, Islamic thinkers always flowed their thoughts in various fields and contributed and greatly influenced the life and intellectuality of Muslims to this day. So, it is important to mention who are the Muslim scholars who have stuck their fangs and brought influence even to all corners of the world. These are 10 of the many Muslim intellectuals whose influence is very large for intellectual progress and the lives of Muslims. The ten figures include Al-Kindi, Al-Asy’ari, Al-Farabi, Ibn Sina, Al-Ghazali, Ibn Rushd, Ibn Taimiyah, Ibn Khaldun, Al-Afghani and Muhammad Abduh. The thoughts and contributions of these 10 figures are summarized in Nurcholish Madjid’s work entitled Khazanah Intelektual Islam. Thus, this paper aims to reveal and analyze critically and analytically what is contained in the book relating to the figures of Muslim intellectuals mentioned above. From the process of reviewing this book, it was found that Cak Nur’s work is quite comprehensive in conveying the intellectual journey of the Islamic world in a coherent manner, especially in the preamble which he compiled with a solid and neat content telling the development of critical thinking of Muslims from the friend of Umar bin Khatab to the modernist figure Muhammad. Abduh. In the following chapters, the main ideas of the ten figures are presented. This work makes it very easy for the reader to grasp the developments and differences of thought among the great figures of Islam.